PipeDoll: A Motion Capture Addon for the Godot Game Engine - Tucker, Ethan (My University, 2023)
Character animation is a key challenge in game development and other fields and is often created using motion capture. However, traditional motion capture requires specialized hardware and can be inaccessible for small teams. For this project, I have developed a 2D motion capture addon for the Godot game engine. The addon uses a machine learning model to perform motion capture using a standard webcam, avoiding the need for hardware. It meets all the key functional requirements identified for the project and is published as open-source software at https://github.com/ectucker1/pipedoll.